Coping strategies in mitigating covid-19 pandemic’s effect on farming household income in Osun state, Nigeria - Kolawole Adelekan Adeloye; Dixon Olutade Torimiro; Damilare Samuel Olufemi (Agropecuária Catarinense, 2023)
Income of farming households with low socio-economic status is a task in emerging nations, rural parts of Nigeria inclusive. In connection with this, the entrance of Covid-19 pandemic posed a grave risk to the economy of the households. This study, therefore, investigate the coping strategies in mitigating Covid-19 pandemic’s effect on the farming households’ income. Data for the paper were collected from 150 farming household heads, through multistage sampling method, with the use of interview scheduled and analysed using appropriate statistics. The findings showed that many (57.3%) of the respondents were male. The widely practiced coping strategies during the pandemic were rationed spending (=2.63), job diversification (=2.40), reduction in hired labour (=2.36), household food rationing (=2.28) among others. There is substantial relationship between household size (r = 0.075, p = 0.003), annual income (r = 0.033, p = 0.004) and coping strategies practiced at p≤0.005.  It was concluded that the pandemic had great effect on the income of the farming household. The study recommends formulation of necessary, effective and urgent policies for assisting and generating fresh employments and revenue producing prospects for affected households.